Effects of targeting eye color in Tenebrio molitor through RNA interference of tryptophan 2, 3‐dioxygenase (vermilion): Implications for insect farming. Issue 1 (25th March 2019) - Oppert, Brenda; Chu, Fu‐Chyun; Reyna, Steven; Pinzi, Sofia; Adrianos, Sherry; Perkin, Lindsey; Lorenzen, Marcé
Abstract: The gene vermilion encodes tryptophan 2, 3‐dioxygenase, part of the ommochrome pathway, and is responsible for the dark pigmented eyes in some insects, including beetles. Using RNA interference, we targeted the vermilion gene ortholog in embryos and pupae of the yellow mealworm, Tenebrio molitor, resulting in larvae and adults, respectively, that lacked eye pigment. RNA‐Seq was used to analyze the impact of vermilion ‐specific RNA interference on gene expression. There was a 425‐fold reduction in vermilion gene expression ( p = 0.0003), as well as significant ( p < 0.05) differential expression of 109 other putative genes, most of which were downregulated. Enrichment analysis of Gene Ontology terms found in the differentially expressed data set included genes known to be involved in the ommochrome pathway. However, enrichment analysis also revealed the influence of vermilion expression on genes involved in protein translocation to the endoplasmic reticulum, signal transduction, G‐protein‐coupled receptor signaling, cell‐cycle arrest, mannose biosynthesis, and vitamin transport. These data demonstrate that knockdown of vermilion in T. molitor results in complete loss of eye color (white‐eyed phenotype) and identify other interrelated genes in the vermilion metabolic pathway. Therefore, a dominant marker system based on eye color can be developed for the genetic manipulation of T. molitor to increase the value of mealworms as an alternative food source by decreasing negative traits, such as disease susceptibility, and increasing desired traits, such as protein content and vitamin production. Abstract : Knockdown of the expression of the gene vermilion in Tenebrio molitor by RNA interference results in white‐eyed adults (left, red circle) compared to the wild‐type black‐eyed adults (right, red circle).